Synthesis of New Dithiocarbamate Derivative Reagent for Micro Extraction and Determination of Iron(II) Ion in Aqueous Solution - Shaker, Ivan Malik; Khudhair, Ahmed Fadhil; Mihsen, Hayder Hamied (Indonesian Journal of Chemistry, 2024)
The new reagent N-methyl-N-((((4-chlorophenyl)diazenyl)thio)carbonothioyl)aniline (L) was synthesized via the reaction of sodium N-methyl-N-phenyldithiocarbamate with 4-chlorobenzenediazonium salt. The reagent was identified with many techniques, such as CHNS elemental analysis, UV-vis spectroscopy, FTIR spectroscopy, mass spectroscopy, 1H-NMR, and 13C-NMR spectroscopy. The Fe(II) ion was utilized to create a metal complex by reacting 2 mol of reagent with 1 mol of iron(II) chloride. Two approaches that were utilized for M:L ratio determination are mole ratio and Job methods. All of these refer to the 1:2 ratio for the complex. The solid complex was prepared and identified with the previous techniques, and additional electrical molar conductivity, and magnetic susceptibility measurements. A tetrahedral structure for the prepared complex was suggested based on spectroscopic measurements and elemental analysis results. Cloud point extraction was created for the preconcentration and separation of Fe(II) in drug samples by forming a rich phase using Triton X-114 at 80 °C temperature and pH 5 measurements utilizing flame atomic absorption spectroscopy and UV-vis spectrophotometer at λmax 635 nm. The calibration curve of Fe(II) was linear in the extent of 0.2–1.0 μg/mL with r2 of 0.996. The detection limit and quantification are 0.0504 and 0.1530 μg/mL.